Can Statin Treatment Reduce the Risk of Hepatocellular Carcinoma? A Systematic Review and Meta-Analysis. (18th June 2020) - Chang, Yue; Liu, Qinyu; Zhou, Zidong; Ding, Yuping; Yang, Mei; Xu, Wei; Chen, Kai; Zhang, Qing; Wang, Zhenguo; Li, Hai
Background: Whether statins can reduce the incidence of cancers has been an interesting topic in recent years. This meta-analysis aimed to determine the relationship between statin treatment with the risk of hepatocellular carcinoma. Methods: Studies published up to July 2019 were screened from databases. The data from approved studies were pooled. Random-effects or fixed-effects model was used to calculate the relative risk with 95% CIs in the overall group and subgroups. Sensitivity and meta-regression analyses were performed, and publication bias was evaluated. Results: A total of 18 studies involving 1 611 596 patients were included in this meta-analysis. The overall result showed a significantly reduced risk of hepatocellular carcinoma (relative risk = 0.54, 95% CI: 0.42-0.66) in statin users. In comparison to the risk in nonstatin users, the risk of hepatocellular carcinoma was reduced in all subgroups. The dose of statins and their pharmacokinetics can partly explain the heterogeneity in the overall meta-analysis ( I 2 = 94.6%, P = .000). A dose-dependent effect of statin use for the reduced risk of hepatocellular carcinoma was found. Conclusions: Findings from this meta-analysis support that statin use can significantly reduce the incidence of hepatocellular carcinoma.